Webinar: digital transformation for future leaders - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School)
A webinar titled "Digital Transformation For Future Leaders" was held on 24 July 2021 (Saturday) from 10:00 AM - 11:30 AM via Zoom. This event was organized by the Arshad Ayub Graduate Business School (AAGBS), UiTM.